Análise de fatores de dor intra-operatória na cirurgia ambulatorial no câncer de mama - Melo, Fernando Yaeda de [UNESP] (2013)
Every day hundreds of women are diagnosed with breast cancer. It is largely responsible for cancer-related deaths among women. The diagnosis of breast cancer has undergone major changes in recent decades. We left a picture of absolute predominance of advanced disease at diagnosis for diagnoses in increasingly early stages. These changes occurred due to mammographic screening programs. We come to realize increasingly ambulatory surgical procedures under local anesthesia, aiming diagnosis of breast cancer at this early stage, subclinical. With this new reality, new concerns, such as the pain and discomfort that may involve such procedures. Several studies have determined predictors that were associated with greater complaints of pain postoperatively these procedures performed in an outpatient setting. And in the case of intraoperative pain? Are there preoperative factors that may predict the intensity of referred pain, intraoperatively in patients undergoing ambulatory surgical procedure under local anesthesia? This was a prospective, controlled, without blinding held at Cancer Hospital in the period from 01/2012 to 01/2013. Data collection was performed by a single trained professional to the questionnaire. The participants completed a questionnaire involving demographics, disease history and anxiety (STAI - Trait Anxiety Inventory-State). At the end of the procedure the surgeons and patients completed a questionnaire with yours perceptions about the procedure. We used the Visual Analogue Scale (VAS) for pain assessment. It was considered as significant pain two cutoffs - VAS ≥ 4 and VAS ≥ 7. 230 patients were evaluated. For cutoff 4 shows biggest complaint of pain in patients with rheumatologic disease (p = 0.01), personal history of breast cancer (p = 0.02), patients undergoing excisional biopsies / incisional biopsies compared guided stereotactic (p = 0.05), more anxiety preoperatively ...